2007
DOI: 10.1080/07420520701800868
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Characteristics of the Circadian Rest‐Activity Rhythm of Cancer In‐Patients

Abstract: The aim of the present study was to evaluate the characteristics of the circadian rest-activity rhythm of cancer patients. Thirty-one in-patients, consisting of 19 males and 12 females, were randomly selected from the Regional Cancer Center, Pandit Jawaharlal Nehru Medical College, Raipur, India. The rest-activity rhythm was studied non-invasively by wrist actigraphy, and compared with 35 age-matched apparently healthy subjects (22 males and 13 females). All subjects wore an Actiwatch (AW64, Mini Mitter Co. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 28 publications
2
47
0
1
Order By: Relevance
“…1a and 2d-f respectively) [31]. This is consistent with the lack of any significant impact on the diurnal pattern of cortisol (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1a and 2d-f respectively) [31]. This is consistent with the lack of any significant impact on the diurnal pattern of cortisol (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Nine other parameters were calculated: three estimating the circadian rest-activity pattern (dichotomy index, I<O [29]; intraday variability, IV; and interday stability, IS [30]), one estimating sleep (sleep fragmentation index, SFI [31]), and five related to physical activity (average activity counts; average duration of rest; a probabilistic metric of activity fragmentation, pAR that is analogous to pRA [27]; average activity during 6 most active hours, M6; and during 6 least active hours, L6). Finally, the actigraph provided two estimates of the phase of the activity pattern using a cosine regression (acrophase) or a non-parametric analysis of the average clock time of the midpoint of the eight most active hours of each day (M8) [32].…”
Section: Assessment Of Sleep and Circadian Rhythmicitymentioning
confidence: 99%
“…Increased comorbidity in our low-RA group is consistent with reduced amplitude of the circadian rest-activity cycle reported in other disease conditions, such as hypertension, 4 cancer, 1 and mood disorders, 46 all conditions taken into account by the COTE index. In their study of schizophrenia patients, Bromundt et al 19 found that low amplitude could be associated with disturbances of circadian rhythms, as shown by a delayed onset of melatonin secretion in relation to sleep time, and they proposed that circadian asynchrony may explain the strong association they found between low amplitude and low scores on many tests of cognitive functions.…”
supporting
confidence: 66%
“…Studies on a variety of medical disorders, including cancer, 1 Alzheimer's disease, 2,3 and hypertension, 4 have found that larger amplitude in rest-activity rhythms is associated with lower disease severity and better prognosis. Rest-activity rhythms are usually measured with continuous actigraphic recordings, a technique that has the advantage of being noninvasive and providing results that are representative of patients' usual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients take longer time to fall asleep, wake up more often, spend more time in bed and nap more frequently than healthy individuals [32,33] . On the other hand, genetic, environmental or behavioral factors may favor circadian disruption, predisposing patients to tumor development [34] .…”
Section: Discussionmentioning
confidence: 99%